EFFECT OF REFERENCE INTEREST RATES, LOANS AMOUNT AND AMOUNT OF THIRD PARTY FUNDS ON NET INTEREST INCOME CASE STUDY: CONVENTIONAL COMMERCIAL BANKS IN INDONESIA - Tandianos, Kevin (Journal Economics & Business Atmajaya Indonesia, 2019)
This study aims to determine the effect of the independent variable (reference interest rate, the amount of credit extended to the public and the amount of third party funds received from the public) on the dependent variable (net interest income at conventional commercial banks in Indonesia). The research method uses multiple linear regression analysis. The stages of the research are determining the multiple linear regression equation, calculation of the coefficient of determination, F test (simultaneous) and t test (partial). The results showed that the most influencing variable Net Interest Income based on the order of the coefficient was the Amount of Credit, Reference Interest Rate and Amount of Third Party Funds. That as much as 91.70% of the factors that influence the independent variables can be explained by the independent variables, while the remaining 8.30% can be explained by other factors outside the variables in this study. And simultaneously or partially all the independent variables play a role in influencing the dependent variable.